Kemampuan Manajerial dan Fungsi Kepemimpinan Direktur Dalam Upaya Meningkatkan Kinerja Dosen di Program Diploma Pelayaran Universitas Hang Tuah Surabaya - Supangat (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2019)
The purpose of this research is to know whether the factor of the lecturer’s manajerial capability and the function of the Director’s leadership at Program Diploma Pelayaran in Universitas Hang Tuah Surabaya have influenced a significant correlation to increase the lecturer’s competency partially and simultaneously. Instead of knowing which has dominant incluence between both of independent variables. By taking 40 lecturers in Program Diploma Pelayaran as being respondens and by using the research method of quantitative description. It is known that the lecturer’s manajerial capability and the function of the Director’s leadership have a significant influence to the lecturer’s competency as simultaneously, while as partially, the lecturer’s manajerial capability has a significance influence and dominant to the lecturer’s competency, however, the function of Director’s leadership has no influence to the lecturer’s competency. So the important implication of this research is necessary to optimalize the function of the Director’s leadership more and improves the lecturer’s manajerial capability through conduct training or upgrade the level of education actively to the each lecturer. And also need to do further research with the same variables.